1992
DOI: 10.1136/oem.49.8.545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupational exposure to mercury vapour on the central nervous system.

Abstract: Possible effects of mercury on the central nervous system (CNS) were examined in a group of chloralkali workers exposed to mercury (n = 89) and compared with a control group (n = 75), by registration of subjective symptoms, personality changes, forearm tremor, and performance on six computerised psychometric tests in the two groups. The groups were similar in age, education, verbal comprehension, and work tasks. In the chloralkali group, median blood mercury concentration (B-Hg) was 55 nmol/l, serum mercury co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 23 publications
1
52
1
6
Order By: Relevance
“…Below 40 µg/l, symptoms are thought to be unlikely. 6 However, a study in Sweden 18 reported central nervous system symptoms involving 96 occupationally exposed individuals with a median mercury level in urine of 25 µg/g creatinine. Another study found renal effects in workers with levels >20 µg/g creatinine.…”
Section: Blood and Urine Analysismentioning
confidence: 99%
“…Below 40 µg/l, symptoms are thought to be unlikely. 6 However, a study in Sweden 18 reported central nervous system symptoms involving 96 occupationally exposed individuals with a median mercury level in urine of 25 µg/g creatinine. Another study found renal effects in workers with levels >20 µg/g creatinine.…”
Section: Blood and Urine Analysismentioning
confidence: 99%
“…11,12 Low concentrations of urinary mercury reported in recent studies of DHCWs 3,13,14 contrast with those published a decade or so ago. [15][16][17] These reductions may be considered to be due to greater awareness of the possible problems caused by excessive mercury intake, the use of automated methods of amalgam preparation and improvements in mercury hygiene in dental surgeries. [18][19][20][21]  One hundred and eighty dental surgeries were tested for environmental mercury.…”
mentioning
confidence: 99%
“…Urine excretion of mercury occurs during and shortly after exposure, thus urine assay can be used to evaluate the mercury exposure and body burden. Although there is no consensus on safe mercury contents in urine, various adverse effects have been reported for workers with chronic mercury exposure who had urine mercury levels of 50 μg/L or less (Barregard et al, 1988;Langworth et al, 1992;Pogarev et al, 1997). Table 2 summarizes the results from an occupational hygiene investigation on replacement of liquid mercury by Ti 3 Hg alloy in mercury dosing at a fluorescent lamp plant in Tianjin, China (Wang, 1993).…”
Section: Health Risk From Mercury In Fluorescent Lamp Manufacturingmentioning
confidence: 99%